East Central Europe in the First Globalization (1850-1914) - Müller, Uwe (Studia Historiae Oeconomicae, 2018)
The article analyzes the position and the positioning strategy of East Central Europe in the so-called “first globalization (1850-1914)”. The focus is on foreign trade and the transfer of the two most important production factors, i.e. capital and labor. East Central Europe included in this period the territories of the Habsburg Monarchy, the Kingdom of Poland as a part of the Russian Empire, and the eastern provinces of the Kingdom of Prussia which were from 1871 onwards part of the German Reich. The article combines the theories and methods of economic history and transnational history. It sees itself as a contribution to a trans-regional history of East Central Europe by analyzing first the main “flows” and then the influence of “controls”. The article analyzes to what extent and in what way East Central Europe was involved in the globalization processes of the late 19th century. It discusses whether East Central Europe was only the object of global developments or even shaped them. In this context it asks about the role of the empires (Habsburg monarchy, German Reich, Russia) for the position of East Central European economies in the world economy. It shows that the economic elites in the centers but also on the edges of the empires developed different strategies for how to respond to the challenges of globalization.